Answer:
(a) k = 30.33 N/m
(b) a = 9.8 m/s²
Step-by-step explanation:
First, we need to find the force acting on the bungee jumper. Since, this is a free fall motion. Therefore, the force must be equal to the weight of jumper:
F = W = mg
F = (65 kg)(9.8 m/s²)
F = 637 N
(a)
Now applying Hooke's Law:
F = k Δx
where,
k = spring constant = ?
Δx = change in length of bungee cord = 33 m - 12 m = 21 m
Therefore,
637 N = k(21 m)
k = 637 N/21 m
k = 30.33 N/m
(b)
Since, this is free fall motion. Thus, the maximum acceleration will be the acceleration due to gravity.
a = g
a = 9.8 m/s²